Prevalence of Allergic Diseases in Children Vaccinated Against Tuberculosis and Hepatitis B in the Early Neonatal Period: Literature Review - Marina V. Fedoseenko; Veronika A. Petrova; Leyla S. Namazova-Baranova (Педиатрическая фармакология, 2021)
Background. T-cell response is shifted towards Th2-type predominance in newborns. This makes them particularly vulnerable to exposure of various external pathogens, development of severe infections, moreover, it is also a risk factor for allergic diseases development. Various methods of switching the immune response to Th1-type are currently under research, and one of them is vaccination.Objective. The aim of the study is to provide data on the prevalence of allergic pathology among children vaccinated against tuberculosis and hepatitis B, as well as the effect of vaccines on immune response type.Results. Data on both increase and decrease in the prevalence of atopic conditions in children vaccinated with BCG and against hepatitis B were analyzed, thus, most of them cannot be considered reliable. The results of several large studies do not reveal any correlation between vaccination and the presence of allergic disease in children. There is data that BCG and hepatitis B vaccines shift the immune response towards Th1-type activation.Conclusion. Vaccination in the early neonatal period may affect switching of the immune response towards Th1-type. That, in turn, can affect the prevalence of allergic pathology in vaccinated children. However, the data available for now is not sufficient to reliably estimate the possible effect of vaccination on atopic conditions manifestation in the future.